Carbon fiber reinforced coating, self-repairing radiation shielding material and preparation method
By constructing a hollow core-shell structure coating of lead tungstate/epoxy resin on the surface of carbon fibers, the problems of gamma radiation shielding and self-healing of fiber-reinforced resin matrix composites in the space environment were solved, thereby improving the radiation shielding performance and self-healing ability of the material.
Patent Information
- Application Number
- CN202510715822.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-11-28
AI Technical Summary
Existing fiber-reinforced resin matrix composites lack gamma radiation shielding capabilities and self-healing functions in space environments, resulting in damage to structural integrity. Furthermore, traditional microcapsule-type self-healing materials have limited effectiveness at the fiber-matrix interface.
A hollow core-shell structure coating of lead tungstate/epoxy resin is constructed on the surface of carbon fiber. The coating is formed by electrochemical method and combined with the curing process of epoxy resin matrix to realize the preparation of self-healing radiation shielding material.
It improves the gamma radiation shielding performance and fracture toughness of the material, which is superior to traditional microencapsulated self-healing materials, and significantly improves the mechanical properties and self-healing effect of the composite material.
Smart Images

Figure CN121021928A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of fiber reinforced resin matrix composite materials, in particular to a carbon fiber reinforced coating, a self-repairing radiation shielding material and a preparation method. BACKGROUND
[0002] With the rapid development of the aerospace industry, the problem of space radiation shielding has attracted widespread attention. Fiber reinforced resin matrix composite materials are often used as structural materials for spacecraft due to their high strength-to-weight ratio, high modulus, corrosion resistance, heat resistance, and thermal stability, and are used in solar panels, space trusses, and cabin skins. However, space environmental factors are one of the main reasons for the degradation of spacecraft structural materials, especially fiber reinforced resin matrix composite materials, which pose a significant threat to the reliability and service life of spacecraft. High-energy charged particle radiation, cold-hot cycling, and space debris are among the main causes of spacecraft performance degradation and damage.
[0003] The resin matrix contains a large amount of H and O elements, which has good shielding effect on high-energy protons and electrons, but poor shielding performance on gamma rays, which can cause total dose effects on electronic components inside the spacecraft, leading to permanent failure of the device. The resin matrix itself is brittle, and high-energy radiation and space debris can also exacerbate the formation of microcracks in the resin. Once the cracks start to expand unstably, the structural integrity of the spacecraft will be severely threatened, and it is also difficult to repair the material in the space environment. Therefore, it is necessary to develop a fiber reinforced resin matrix gamma radiation shielding material with self-repairing ability to ensure that the material has excellent fracture toughness and gamma radiation shielding ability. Currently, there is no report of a fiber reinforced resin matrix gamma radiation shielding material with self-repairing function and radiation protection function. SUMMARY
[0004] In order to solve the above-mentioned deficiencies in the prior art, the present application aims to provide a carbon fiber reinforced coating, a self-repairing radiation shielding material and a preparation method.
[0005] According to an aspect of the present application, a carbon fiber reinforced coating is provided, comprising: a lead tungstate / epoxy resin carbon fiber reinforced coating. The lead tungstate is used as a shell layer to form a hollow core-shell structure on the surface of the carbon fiber.
[0006] According to some embodiments of the present application, the carbon fiber is a continuous carbon fiber cloth.
[0007] According to a second aspect of the present application, a preparation method of the above-mentioned carbon fiber reinforced coating is also provided, comprising: According to the following weight parts, 2-5 parts of sodium hydroxide, 10-15 parts of styrene maleic anhydride copolymer, 100 parts of epoxy resin, 90-110 parts of lead acetate, 70-90 parts of sodium tungstate, and 30-40 parts of ammonium chloride are used as raw materials to configure the electroplating solution; The pretreated continuous carbon fiber cloth is immersed in the electroplating solution; The electroplating is performed with the continuous carbon fiber cloth as a cathode and a tungsten plate as an anode to obtain the carbon fiber reinforced coating.
[0008] According to some embodiments of the present application, the electroplating solution is configured by adding sodium hydroxide, styrene maleic anhydride copolymer, and epoxy resin into deionized water, stirring and emulsifying; The lead acetate solution is added into the emulsified epoxy resin emulsion, and after stirring, the sodium tungstate solution and the ammonium chloride solution are added, and the electroplating solution is obtained after stirring.
[0009] According to some embodiments of the present application, the epoxy resin includes but is not limited to E44, E51, E55, E31, and E20 epoxy resin.
[0010] According to some embodiments of the present application, the continuous carbon fiber cloth is treated with acetone, soaked, and washed with deionized water to obtain the pretreated continuous carbon fiber cloth.
[0011] According to a third aspect of the present application, a self-repairing radiation shielding material is provided, which contains the carbon fiber reinforced coating described above and / or the carbon fiber reinforced coating prepared by the preparation method described above. Optionally, the hollow part of the carbon fiber reinforced coating is filled with a healing agent.
[0012] According to another aspect of the present application, a preparation method of a self-repairing radiation shielding material is also provided, which includes: The epoxy resin matrix is preheated to reduce the viscosity to 300-500 mPa·s; The epoxy resin matrix is mixed with a curing agent and a toughening agent according to a mass ratio of (2-2.5):1:(0.1-0.4) to obtain a resin system; The resin system is filled into the carbon fiber reinforced coating described above under a negative pressure condition of -0.095 to -0.098 MPa; The negative pressure condition is maintained to perform an initial stage of resin gelation; heating is performed to make the resin system form a three-dimensional network skeleton and complete crosslinking to obtain the self-repairing radiation shielding material; According to some embodiments of the present application, the heating includes: a first stage of heating at a rate of 2-3 ℃ / min to 80-90 ℃, and holding for 1-2 h to make the resin preliminarily gelate to form a three-dimensional network skeleton; and a second stage of heating to 120-130 ℃, and holding for 2-3 h to complete the main crosslinking reaction.
[0013] According to some embodiments of the present application, the epoxy resin matrix includes but is not limited to E44, E51, E55, E31, E20 epoxy resin matrix; According to some embodiments of the present application, the curing agent is methyl tetrahydrophthalic anhydride; the toughening agent is FX320.
[0014] Compared with the prior art, the present application at least includes the following beneficial effects: The present application provides a carbon fiber reinforced coating, a self-repairing radiation shielding material, selects lead tungstate as the carbon fiber reinforced coating shell layer on the surface of the carbon fiber, as an inorganic shell layer, so that the carbon fiber has gamma radiation shielding capability and stronger thermal stability; selects epoxy resin as the core material of the carbon fiber reinforced coating on the surface of the carbon fiber, which can not only copolymerize with the matrix resin to enhance the fracture toughness of the resin, but also cooperate with the curing agent to make the resin have a self-repairing function.
[0015] The present application improves the self-repairing performance and radiation shielding performance of the carbon fiber by constructing a carbon fiber reinforced coating on the surface of the carbon fiber. The fiber reinforced phase itself has a large surface, and the lead tungstate / epoxy resin carbon fiber reinforced coating prepared on the surface of the fiber can obviously improve the radiation shielding performance of the material, and the coating has good bonding force with the surface of the fiber, which can guarantee the mechanical properties of the composite material. In addition, the crack initiation site in the fiber reinforced resin matrix composite material often occurs at the interface between the fiber and the matrix. The carbon fiber reinforced coating of the present application is a hollow micro-coating, and its self-repairing effect is better than that of the traditional microcapsule type self-repairing material. BRIEF DESCRIPTION OF DRAWINGS
[0016] Figure 1 The present application is a schematic diagram of the structure of the carbon fiber reinforced coating, self-repairing radiation shielding material: (a) three-dimensional structure diagram; (b) detailed interface structure of the two-dimensional section of the coating.
[0017] Figure 2 The present application is a micro-SEM and EDS diagram of the carbon fiber reinforced coating.
[0018] Figure 3 The present application is an XRD diagram of the carbon fiber reinforced coating.
[0019] Figure 4 The present application is an FTIR diagram of the carbon fiber reinforced coating, epoxy resin, lead tungstate.
[0020] Figure 5 The present application is a DSC diagram of the carbon fiber reinforced coating, epoxy resin.
[0021] Figure 6 The present application is a TGA, DTG diagram of the carbon fiber reinforced coating, epoxy resin.
[0022] Figure 7The images show the fracture strength of different composite materials before and after fracture repair. Lighter colors represent the fracture strength before repair, while darker colors represent the fracture strength after repair.
[0023] Figure 8 This is a diagram showing the photon transmittance of the self-healing radiation shielding material of this application under different energy gamma radiation.
[0024] Figure 9 The graph shows the linear attenuation coefficients of shielding materials with different carbon fiber reinforced coating contents under different energy gamma radiation. Detailed Implementation
[0025] The technical solution of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0026] It should be particularly noted that similar substitutions and modifications made to this application are obvious to those skilled in the art, and they are all considered to be included in this application. Those skilled in the art can obviously make modifications or appropriate alterations and combinations to the methods and applications described herein without departing from the content, spirit, and scope of this application to implement and apply the technology of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments.
[0027] Unless otherwise specified, this application shall be made in accordance with conventional conditions or conditions recommended by the manufacturer. The raw materials or excipients used, as well as the reagents or instruments used, whose manufacturers are not specified, are all conventional products that can be obtained commercially.
[0028] The following is a detailed description of this application.
[0029] Fiber-reinforced resin matrix composites possess the advantages of being lightweight and high-strength, but they do not inherently possess gamma-ray shielding capabilities. Generally, they are reinforced by adding metallic functional fillers, utilizing the gamma-ray shielding properties of heavy metals to improve the radiation shielding performance of the composite material. However, the addition of metallic fillers reduces the fluidity of the resin matrix and the interfacial properties between the resin and the fiber reinforcement phase. Therefore, to ensure the mechanical properties of the composite material, the amount of metallic filler added is limited.
[0030] For self-healing composite materials, existing research includes microencapsulation, hollow fiber, and microvascular network types. Among these, microencapsulation technology is the most mature. Its principle involves filling a healing agent into a shell to form micron-sized microcapsules, which are then dispersed in a matrix resin. When microcracks appear in the matrix, the crack tip breaks the microcapsule shell, and the healing agent flows to the crack under capillary action, undergoing a curing reaction with the resin matrix and bonding together, thus achieving self-healing. In fiber-reinforced resin matrix composites, cracks often originate at the fiber-matrix interface, thus limiting the effectiveness of these microencapsulation self-healing materials. Hollow fiber types, generally using glass fibers, offer limited enhancement to the mechanical properties of the composite material.
[0031] This application improves the self-healing and radiation shielding properties of carbon fibers by constructing a carbon fiber reinforced coating on the surface of carbon fibers. The fiber reinforcement phase itself has a large surface area, and the lead tungstate / epoxy resin carbon fiber reinforced coating prepared on its surface significantly improves the radiation shielding performance of the material. Furthermore, the coating has excellent adhesion to the fiber surface, ensuring the mechanical properties of the composite material. In addition, crack initiation sites in fiber-reinforced resin matrix composites often occur at the fiber-matrix interface, and the self-healing effect of the carbon fiber reinforced coating is superior to that of traditional microencapsulated self-healing materials.
[0032] This application achieves the preparation of hollow lead tungstate microcoatings on continuous carbon fiber fabric via an electrochemical method. In conventional chemical deposition methods, lead tungstate and the healing agent spontaneously form micron-sized core-shell microspheres, which cannot be uniformly coated onto the surface of continuous carbon fiber fabric. While ordinary electrochemical methods can form a lead tungstate coating on the carbon fiber fabric surface, the healing agent is electrically neutral and therefore cannot form a hollow microcoating. This application, through chemical modification, establishes a bond between the healing agent and tungsten ions. During the electrochemical process, both simultaneously reach the carbon fiber surface and self-assemble under polarity to form a hollow microcoating structure, resulting in strong adhesion between the coating and the fiber surface.
[0033] The technical solution of this application will be further described below with reference to specific embodiments.
[0034] Example 1 Preparation of carbon fiber reinforced coating: Electroplating solution preparation: In a 100 mL beaker, add 0.29 g sodium hydroxide, 1.45 g styrene-maleic anhydride copolymer (SMA), and 10 g E51 epoxy resin to 75 mL deionized water and stir at 100-200 rpm for 10-20 min at 80°C. Place the emulsion on an emulsifier and stir at 16,000 rpm for 3 min. Transfer the emulsified epoxy resin emulsion to a 500 mL three-necked flask and stir magnetically at 80°C. Add lead acetate (Pb(CH3COOH)2·3H2O) solution (9.63 g, 140 mL) and stir at 500 rpm for 3 h. Add sodium tungstate (Na2WO4·2H2O) solution (8.35 g, 140 mL) and ammonium chloride (NH4Cl) solution (3.46 g, 40 mL) and stir at 500 rpm for 8 h to obtain the electroplating solution. Electroplating: Continuous carbon fiber cloth was treated with acetone and soaked for 1 hour. After rinsing with deionized water, it was immersed in the prepared electroplating solution, which was then subjected to ultrasonic vibration at 30 kHz. The carbon fiber cloth was used as the cathode, and a tungsten plate as the anode, maintaining a cathode current density of 20 A·cm⁻¹. 2 The thickness of the hollow layer is controlled by controlling the electroplating time; the carbon fiber cloth is washed three times with deionized water and anhydrous ethanol and dried in a 60°C drying oven for 48 hours to obtain the hollow micro-coating, which is the carbon fiber reinforced coating of this application.
[0035] Preparation of self-healing radiation shielding materials: Resin preparation: Preheat the E44 epoxy resin matrix (40-50℃) to reduce the viscosity to 300-500 mPa·s, promoting its penetration in the flow network; mix the resin system with A50 curing agent (methyltetrahydrophthalic anhydride) and toughening agent (FX320) in a ratio of 2:1:0.1, and mix thoroughly before use. Impregnation: The carbon fiber reinforced coating is laid out according to the shape requirements. After the mold is clamped, the vacuum pump is started to form a stable negative pressure (-0.095 to -0.098 MPa) in the mold cavity. The resin injection port valve is opened, and the pressure difference drives the resin to spread rapidly along the guide net to the edge of the mold cavity. The resin is vertically penetrated into the fiber layer below from the guide net. When the resin completely fills the mold cavity, the vacuum negative pressure is maintained for 20-30 minutes to promote the rise of micro bubbles to the surface of the guide net and discharge them through the vacuum pipeline. The injection port is closed and the vacuum is maintained until the initial stage of resin gelation.
[0036] Curing: The temperature is raised by the built-in heating plate. In the initial stage, the temperature is raised to 80-90℃ at a rate of 2-3℃ / min and held for 1-2 hours to allow the resin to initially gel and form a three-dimensional network skeleton. In the second stage, the temperature is raised to 120-130℃ and held for 2-3 hours to complete the main cross-linking reaction. After curing, the product is naturally cooled to below 60℃ in the mold and then demolded to obtain the self-repairing radiation shielding material.
[0037] Example 2 Preparation of carbon fiber reinforced coating: Electroplating solution preparation: In a 250 mL beaker, add 0.95 g sodium hydroxide, 3.0 g styrene-maleic anhydride copolymer (SMA), and 25 g AFG-90# epoxy resin to 180 mL of deionized water and stir at 70°C. Place the emulsion on an emulsifier and stir at 16,000 rpm for 5 min. Transfer the emulsified epoxy resin emulsion to a 1500 mL three-necked flask and stir magnetically at 80°C. Add lead acetate (Pb(CH3COOH)2·3H2O) solution (22.75 g, 350 mL) and stir at 500 rpm for 2 h. Add sodium tungstate (Na2WO4·2H2O) solution (22.5 g, 350 mL) and ammonium chloride (NH4Cl) solution (8.75 g, 100 mL) and stir at 500 rpm for 8 h to obtain the electroplating solution. Electroplating: Continuous carbon fiber cloth was treated with acetone and soaked for 1 hour. After rinsing with deionized water, it was immersed in the prepared electroplating solution, which was then subjected to ultrasonic vibration at 30 kHz. The carbon fiber cloth was used as the cathode, and a tungsten plate as the anode, maintaining a cathode current density of 20 A·cm⁻¹. 2 The thickness of the hollow layer is controlled by controlling the electroplating time; the carbon fiber cloth is washed five times with deionized water and anhydrous ethanol and dried in a 60°C oven for 60 hours to obtain the hollow micro-coating, which is the carbon fiber reinforced coating of this application.
[0038] Preparation of self-healing radiation shielding materials: Resin preparation: Preheat the E31 epoxy resin matrix (40-50℃) to reduce the viscosity to 300-500 mPa·s to promote its penetration in the flow network; mix the resin system with A50 curing agent (methyltetrahydrophthalic anhydride) and toughening agent (FX320) in a ratio of 2.5:1:0.3, and mix thoroughly before use. Impregnation: The carbon fiber reinforced coating is laid out according to the shape requirements. After the mold is clamped, the vacuum pump is started to form a stable negative pressure (-0.095 to -0.098 MPa) in the mold cavity. The resin injection port valve is opened, and the pressure difference drives the resin to spread rapidly along the guide net to the edge of the mold cavity. The resin is vertically penetrated into the fiber layer below from the guide net. When the resin completely fills the mold cavity, the vacuum negative pressure is maintained for 20-30 minutes to promote the rise of micro bubbles to the surface of the guide net and discharge them through the vacuum pipeline. The injection port is closed and the vacuum is maintained until the initial stage of resin gelation.
[0039] Curing: The temperature is raised by the built-in heating plate. In the initial stage, the temperature is raised to 80-90℃ at a rate of 2-3℃ / min and held for 1-2 hours to allow the resin to initially gel and form a three-dimensional network skeleton. In the second stage, the temperature is raised to 120-130℃ and held for 2-3 hours to complete the main cross-linking reaction. After curing, the product is naturally cooled to below 60℃ in the mold and then demolded to obtain the self-repairing radiation shielding material.
[0040] Examples 3-5 Self-healing radiation shielding materials with different carbon fiber reinforced coating contents (based on the weight of carbon fiber cloth) were prepared according to the preparation method of the above embodiments. The contents of Examples 1-5 are shown in the table below:
[0041] Comparative Example 1 Preparation of microcapsules: Lead acetate (Pb(CH3COOH)2·3H2O) solution (9.63g, 140mL), sodium tungstate (Na2WO4·2H2O) solution (8.35g, 140mL), and ammonium chloride (NH4Cl) solution (3.46g, 40mL) were added to 200mL of DMF and mixed evenly. After stirring at 500rpm for 3h, 10g of E51 epoxy resin was added and emulsified and stirred at 16,000rpm for 20min to obtain epoxy resin emulsion. After standing at 80℃ for 2h, vacuum filtration and drying were performed to obtain lead tungstate / epoxy resin microcapsule powder. Matrix preparation: The E44 epoxy resin matrix was preheated (40-50℃) to reduce its viscosity to 300-500 mPa·s, promoting its penetration into the flow network; A50 curing agent (methyltetrahydrophthalic anhydride) and toughening agent (FX320) were mixed into the resin system at a ratio of 2:1:0.1 and thoroughly mixed. The prepared lead tungstate / epoxy resin microcapsule powder was then added, ensuring that the resin viscosity did not exceed 800 mPa·s after the powder was added. Impregnation: Lay the carbon fiber cloth according to the shape requirements. After the mold is clamped, start the vacuum pump to form a stable negative pressure (-0.095 to -0.098 MPa) in the mold cavity. Open the resin injection port valve and use the pressure difference to drive the resin to spread rapidly along the guide net to the edge of the mold cavity. The resin penetrates vertically into the fiber layer below from the guide net. When the resin completely fills the mold cavity, maintain the vacuum negative pressure for 20-30 minutes to promote the rise of micro bubbles to the surface of the guide net and discharge them through the vacuum pipeline. Close the injection port and continue to maintain the vacuum until the initial stage of resin gelation.
[0042] Curing: The temperature is raised by the built-in heating plate. In the initial stage, the temperature is raised to 80-90℃ at a rate of 2-3℃ / min and held for 1-2 hours to allow the resin to initially gel and form a three-dimensional network skeleton. In the second stage, the temperature is raised to 120-130℃ and held for 2-3 hours to complete the main cross-linking reaction. After curing, the product is naturally cooled to below 60℃ in the mold and then demolded to obtain the self-repairing radiation shielding material.
[0043] In the comparative examples described above, the lead tungstate / epoxy resin microcapsule powder was pre-added to the epoxy resin matrix. This addition affected the flowability of the resin matrix. When preparing large components, the amount of microcapsule powder added was limited to ensure molding quality, thus restricting the improvement of the composite material's radiation shielding and self-healing properties. Furthermore, the lead tungstate / epoxy resin microcapsules were mainly dispersed within the epoxy resin matrix and could not form a core-shell structure on the carbon fiber surface. Therefore, there was no enrichment at the carbon fiber interface, and since cracks mainly occur at the interface, the repair effect was not as good as in Examples 1 and 2 of this application.
[0044] Experimental Example The carbon fiber reinforced coating and self-healing radiation shielding material prepared in the above embodiments were subjected to morphological analysis and performance testing.
[0045] like Figure 2 The figure shows the morphology and energy dispersive spectroscopy (EDS) analysis. It is clear from the figure that the carbon fiber reinforcement coating on the carbon fiber surface has a core-shell structure. Combined with the EDS surface scanning experimental results, it can be found that the carbon fiber has a micron-sized hollow coating, the outer shell of which contains lead and tungsten, while the core material is mainly composed of carbon and oxygen.
[0046] like Figure 3 As shown, the diffraction peaks of the carbon fiber reinforced coating appear at 2θ = 27.45°, 29.71°, 32.80°, 44.84°, and 55.36°, corresponding to the (112), (004), (200), (204), and (312) crystal planes of the tetragonal carbon fiber reinforced coating, respectively. The results indicate the presence of lead tungstate in the carbon fiber reinforced coating.
[0047] like Figure 4 As shown, the lead tungstate / epoxy resin carbon fiber reinforced coating exhibits characteristic peaks similar to those of epoxy resin and lead tungstate. Among them, the 1474 cm⁻¹ peak is particularly prominent. -1 2850cm -1 2916cm -1 The peak at 779 cm⁻¹ belongs to the characteristic peaks of -CH₃ and -CH₂, confirming the presence of epoxy resin. -1 The characteristic peak at [location] corresponds to the stretching vibration of WO in lead tungstate. These results indicate that the carbon fiber reinforced coating consists of epoxy resin and lead tungstate.
[0048] like Figure 5As shown, within the temperature range of 50-500℃, the carbon fiber reinforced coating of this application exhibits a distinct exothermic and endothermic peak. The exothermic peak at approximately 326℃ is due to the rapid polymerization reaction of the residual anhydride substances (styrene-maleic anhydride copolymer) in the shell and the core at high temperatures. The slight endothermic peak at approximately 360℃ is caused by the further decomposition of residual substances in the carbon fiber reinforced coating.
[0049] like Figure 6 As shown, the decomposition temperature and maximum weight loss temperature of epoxy resin at 5% weight loss are 247.1℃ and 320.9℃, respectively. The carbon fiber reinforced coating of this application has these temperatures of 334.3℃ and 350.1℃, respectively. The presence of the inorganic lead tungstate shell layer inhibits the decomposition of epoxy resin and enhances its heat resistance. The results indicate that the carbon fiber reinforced coating possesses good thermal stability.
[0050] like Figure 7 As shown, the addition of 2.5 wt%, 5.0 wt%, 7.5 wt%, 10.0 wt%, and 12.5 wt% hollow micro-coatings improved the fracture toughness of the composite material by 17.5%, 37.3%, 45.1%, 27.6%, and 66.5%, respectively. After material fracture, the two fracture surfaces of the sample were tightly fitted together, clamped, and then placed in an oven at 200°C for 1 hour. The composite materials with the addition of 2.5 wt%, 5.0 wt%, 7.5 wt%, 10.0 wt%, and 12.5 wt% hollow micro-coatings showed a recovery in fracture toughness of 22.6%, 30.4%, 56.0%, 6.5%, and 5.0%, respectively. These results demonstrate that compared to pure carbon fiber reinforced epoxy resin composites and carbon fiber reinforced epoxy resin composites with added microcapsules, the composite material with the carbon fiber reinforcing coating of this application exhibits higher fracture toughness. The material of this application has significant toughening and self-healing effects.
[0051] like Figure 8 As shown, at the same gamma radiation energy, the photon transmittance, calculated as emitted photon / incident photon (I / I0), decreases with increasing sample thickness. With increasing thickness, incident photons need to pass through a longer shielding material, resulting in a greater attenuation rate. For samples of the same thickness, the shielding capability weakens with increasing gamma radiation energy. This means that high-energy photons are more difficult to shield than low-energy photons.
[0052] like Figure 9As shown, the gamma shielding performance of composite materials with different carbon fiber reinforced coating contents under different gamma radiation energies is reflected by the linear attenuation coefficient and the mass attenuation coefficient. The linear attenuation coefficient increases with increasing carbon fiber reinforced coating content. At energies of 80, 356, and 662 keV, the minimum values are 0.21546, 0.21319, and 0.20293 cm⁻¹, respectively. -1 The maximum values were 0.63185, 0.37796, and 0.22619 cm, respectively. -1 Compared to pure resin, the composite material exhibits significantly improved gamma radiation shielding capabilities at energies of 80, 356, and 662 keV. This result can be attributed to the uniform dispersion of a carbon fiber reinforcement coating with lead tungstate on the carbon fiber surface, which increases the opportunity for interaction with photons and enhances the attenuation coefficient of the composite material. The results demonstrate that a carbon fiber reinforcement coating can significantly improve the gamma radiation shielding performance of the composite material.
[0053] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of this application. It should be noted that, for those skilled in the art, several improvements and modifications can be made to this application without departing from the principles of this application, and these improvements and modifications also fall within the protection scope of the claims of this application.
Claims
1. A carbon fiber reinforced coating, characterized in that, include: Lead tungstate / epoxy carbon fiber reinforced coating; In this process, lead tungstate is used as the shell layer to form a hollow core-shell structure on the surface of the carbon fiber.
2. The carbon fiber reinforced coating according to claim 1, characterized in that, The carbon fiber is a continuous carbon fiber cloth.
3. A method for preparing the carbon fiber reinforced coating according to claim 1 or 2, characterized in that, include: An electroplating solution is prepared using the following raw materials in parts by weight: 2-5 parts sodium hydroxide, 10-15 parts styrene-maleic anhydride copolymer, 100 parts epoxy resin, 90-110 parts lead acetate, 70-90 parts sodium tungstate, and 30-40 parts ammonium chloride. The pretreated continuous carbon fiber cloth is immersed in the electroplating solution; Using the continuous carbon fiber cloth as the cathode and the tungsten plate as the anode, electroplating is performed to obtain a carbon fiber reinforced coating.
4. The method for preparing the carbon fiber reinforced coating according to claim 3, characterized in that, The electroplating solution is prepared by adding sodium hydroxide, styrene-maleic anhydride copolymer and epoxy resin to deionized water, stirring and emulsifying. Lead acetate solution was added to the emulsified epoxy resin emulsion, and after stirring, sodium tungstate solution and ammonium chloride solution were added and stirred to obtain the electroplating solution.
5. The method for preparing the carbon fiber reinforced coating according to claim 4, characterized in that, The epoxy resin is selected from E51, E55, E31 or E20 epoxy resin.
6. The method for preparing the carbon fiber reinforced coating according to claim 4, characterized in that, The continuous carbon fiber cloth is treated with acetone, soaked, and washed with deionized water to obtain the pretreated continuous carbon fiber cloth.
7. A self-healing radiation shielding material, characterized in that, The coating contains the carbon fiber reinforced coating of claim 1 or 2, and / or the carbon fiber reinforced coating prepared by any of the preparation methods of claims 3-6.
8. The self-healing radiation shielding material according to claim 7, characterized in that, The hollow portion of the carbon fiber reinforced coating is filled with a healing agent.
9. A method for preparing a self-healing radiation shielding material, characterized in that, include: Preheat the epoxy resin matrix to reduce its viscosity to 300-500 mPa·s; The epoxy resin matrix, curing agent, and toughening agent are mixed at a mass ratio of (2-2.5):1:(0.1-0.4) to obtain a resin system; Under a negative pressure of -0.095 to -0.098 MPa, the resin system is filled into the carbon fiber reinforced coating of claim 1 or 2, and / or the carbon fiber reinforced coating prepared by any of the preparation methods of claims 3-6; Maintaining the negative pressure conditions, the initial stage of resin gelation is carried out; Heating causes the resin system to form a three-dimensional network skeleton and completes cross-linking, resulting in the self-healing radiation shielding material. Optionally, the heating includes: a first stage of heating to 80-90°C at a rate of 2-3°C / min, and holding at that temperature for 1-2 hours to allow the resin to initially gel and form a three-dimensional network skeleton; In the second stage, the temperature is raised to 120-130℃ and held for 2-3 hours to complete the main cross-linking reaction.
10. The method for preparing the self-healing radiation shielding material according to claim 9, characterized in that, The epoxy resin matrix is selected from E44, E51, E55, E31 or E20 epoxy resin matrix; Optionally, the curing agent is methyltetrahydrophthalic anhydride; the toughening agent is FX320.